What We Think Others Think and Do About Climate Change: A Multicountry Test of Pluralistic Ignorance and Public-Consensus Messaging - Geiger, Sandra J.; Köhler, Jana K.; Delabrida, Zenith N. C.; Garduño-Realivazquez, Karla A.; Haugestad, Christian A. P.; Imada, Hirotaka; Iyer, Aishwarya; Maharja, Carya; Mann, Daniel C.; Marczak, Michalina; Melville, Olivia; Nijssen, Sari R. R.; et al. (Psychological Science, 2025)
Most people believe in human-caused climate change, yet this public consensus can be collectively underestimated ( pluralistic ignorance ). Across two studies using primary data ( n = 3,653 adult participants; 11 countries) and secondary data ( n s = 60,230 and 22,496 adult participants; 55 countries), we tested (a) the generalizability of pluralistic ignorance about climate-change beliefs, (b) the effects of a public-consensus intervention on climate action, and (c) the possibility that cultural tightness-looseness might serve as a country-level predictor of pluralistic ignorance. In Study 1, people across 11 countries underestimated the prevalence of proclimate views by at least 7.5% in Indonesia (90% credible interval, or CrI = [5.0, 10.1]), and up to 20.8% in Brazil (90% CrI = [18.2, 23.4]. Providing information about the actual public consensus on climate change was largely ineffective, except for a slight increase in willingness to express one’s proclimate opinion, δ = 0.05 (90% CrI = [−0.02, 0.11]). In Study 2, pluralistic ignorance about willingness to contribute financially to fight climate change was slightly more pronounced in looser than tighter cultures, highlighting the particular need for pluralistic-ignorance research in these countries.